A Multiperspective Approach to Solvent Regulation of Enzymatic Activity: HMG‐CoA Reductase. (21st December 2017) - Dirkmann, Michael; Iglesias‐Fernández, Javier; Muñoz, Victor; Sokkar, Pandian; Rumancev, Christoph; von Gundlach, Andreas; Krenczyk, Oktavian; Vöpel, Tobias; Nowack, Julia; Schroer, Martin A.; Ebbinghaus, Simon; Herrmann, Christian; et al.
Abstract: 3‐Hydroxy‐3‐methylglutaryl–coenzyme A (HMG‐CoA) reductase was investigated in different organic cosolvents by means of kinetic and calorimetric measurements, molecular dynamics simulations, and small‐angle X‐ray scattering. The combined experimental and theoretical techniques were essential to complement each other's limitations in the investigation of the complex interaction pattern between the enzyme, different solvent types, and concentrations. In this way, the underlying mechanisms for the loss of enzyme activity in different water‐miscible solvents could be elucidated. These include direct inhibitory effects onto the active center and structural distortions. Abstract : Enzyme catalysis in solvent mixtures : Most proteins are rapidly degraded in the presence of organic cosolvents. In this multiperspective study, the molecular interactions that lead to the decrease (or increase) of enzyme activity are investigated for a 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMG‐CoA) reductase model.